The effect of neck-trunk stabilization exercises in cerebral palsy: randomized controlled trial - (:unkn) unknown (My University, 2021)
BACKGROUND: To investigate the effects of neck and trunk stabilization exercises on communication, speech performance, activities of daily living and quality of life in children with cerebral palsy (CP). METHODS: In this prospective, single-blinded, randomized controlled trial, forty children with CP were randomly assigned to Study and Control groups. The study group was received structured neck and trunk stabilization exercises in addition to NDT-B approach. Control group was received NDT-B approach. An oral-motor rehabilitation/therapy was trained to all children. Both groups' trainings were provided for six weeks, with a 45-minute session two times a week. Outcome measures were Communication Function Classification System and Visual Analogue Scale to evaluate communication level; Katz Scale to measure activities of daily living; Viking Speech Scale (VSS) to classify children's speech performance and Pediatric Quality of Life Inventory (PedsQL) to measure the quality of life. RESULTS: The results showed that the communication level and Physical Functioning Score of PedsQL are increased significantly in the study group. VSS is found higher than control at 18th weeks for long term follow up in the study group. CONCLUSIONS: This study highlights the positive effects of stabilization exercises on children's speech performance, Physical Functioning of PedsQL and communication level. Additionally, children' communication skills between them and their caregivers have affected positively and so that this situation provides more qualified daily lives to the children.